Author Correction: Targeted inhibition of STAT/TET1 axis as a therapeutic strategy for acute myeloid leukemia - Xi Jiang (Nature Portfolio, 2018)
The original version of this Article contained an error in the spelling of the author James C. Mulloy, which was incorrectly given as James Mulloy. This has now been corrected in both the PDF and HTML versions of the Article.